Photon-counting CT in maxillofacial and temporal bone CT—a comparative analysis of image quality and dose with high-end energy-integrating CT systems - Yannik Christian Layer; Narine Mesropyan; Alexander Isaak; Dmitrij Kravchenko; Leon Bischoff; Claus C. Pieper; Patrick Kupczyk; Julian A. Luetkens; Benjamin P. Ernst; Daniel Kuetting (European Radiology Experimental)
Abstract Background This experimental study aimed to compare the image quality of maxillofacial and temporal bone imaging using different radiation dose settings on current high-end CT systems: photon-counting detector CT (PCDCT), dual-source energy-integrating detector CT (DECT), and dual-layer spectral detector CT (SDCT). Materials and methods CT scans of a cadaveric human specimen were investigated. Temporal bone imaging was performed with the following parameters: 120 kV and A (high-dose): 140–100 mAs; B (middle-dose): 90–60 mAs; C (low-dose): 50–25 mAs; D (ultra-low-dose): 20–10 mAs. Similarly, for maxillofacial CT: 100 kV and A: 100–80 mAs; B: 70–50 mAs; C: 40–25 mAs; D: 20–10 mAs. Region of interest (ROI)-based noise, SNR, and CNR ratios were calculated for objective assessment of image quality. Subjectively, image quality (IQ) of important anatomic landmarks was assessed using a Likert grading scale from 1 (non-diagnostic) to 5 (excellent). Results For temporal bone, PCDCT provided excellent-to-good IQ up to low-dose scans for all anatomical landmarks, which was superior to SDCT (excellent-to-sufficient), followed by DECT (good-to-poor): e.g., for C: 4.3 ± 0.5 versus 3.7 ± 0.6 versus 2.9 ± 0.6, p < 0.001. PCDCT had significantly better IQ compared to SDCT in ultra-low-dose settings (D: 3.9 ± 0.4 versus 2.8 ± 0.4, p < 0.001). For maxillofacial CT, no significant differences in IQ were found between all CT systems using high- and middle-dose scans, e.g., B: 3.9 ± 0.5 versus 3.8 ± 0.7 versus 3.8 ± 0.4 (p = 0.81). In low- and ultra-low-dose settings, IQ was similar by PCDCT and SDCT (C: p = 0.17; D: p = 0.99) and superior to that of DECT (C: p < 0.05). Conclusion PCDCT offers excellent image quality for temporal bone and maxillofacial CT even at ultra-low doses; results were, in some cases, superior to SDCT and DECT. Relevance statement As PCDCT outperformed modern DECT and SDCT in assessment of maxillofacial and temporal bone CT for image quality and radiation dose, our study suggests that the implementation of PCDCT will improve image quality while reducing radiation exposure in general population. Key Points This work compares the quality of maxillofacial and temporal bone imaging in PCDCT, DECT, and SDCT. Scans of a cadaveric human specimen were investigated using different radiation doses. PCDCT offers excellent image quality for temporal bone and maxillofacial CT. PCDCT, SDCT, and DECT all showed good image quality overall. Graphical Abstract